Project-Based Management Technique for Radiofrequency Spectrum Planning and Allocation: Part Two: The Project Management Plan - J Kerans , Andrew (Journal of Telecommunications and the Digital Economy, 2020)
Spectrum Management is the regulatory action of defining the use of the radiofrequency spectrum. Often this requires the clearance of a large number of incumbent systems to make way for new technologies such as Fourth Generation Mobile Broadband (4G). While great economic benefits may be derived from the new technologies the clearance of any band will come at a cost. It is important both costs and benefits be quantified and compared. In many Administrations, including Australia, these processes are carried out without a defined project management structure. In a series of two papers the Authors combine over 40 years of radio systems and planning experience to suggest a methodology for project-based management of spectrum planning activities. This paper provides an outline of a recommended project management plan structure and references that may be useful to spectrum planners throughout ITU- Region 3; the Asia-Pacific.